2019
DOI: 10.1111/jav.01855
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity in breeding plumage signals in both sexes of a migratory bird: responses to breeding conditions

Abstract: Adaptive phenotypic plasticity may respond to present ambient conditions. Sexual and social signals in both sexes may express phenotype performance. Plumage signals that change discontinuously allow relating discrete variation to previous performance. Both sexes of the pied flycatcher Ficedula hypoleuca present white patches on the wings and on the forehead, which constitute sexual and social signals. Forehead patches are moulted together with body plumage in Africa, while wing patches are partly moulted in Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Conversely, males may prioritize allocating resources to ornamentation, even in suboptimal environmental or physiological condition, because they have the most to gain from sexual ornamentation, in the form of attracting mates and increasing paternity rates. According to this view, bill color in American gold nches (Spinus tristis) was found to re ect individual differences in female immune function but not in males, who consistently invest in bill coloration irrespective of immune function 12 , and a recent eld study with pied ycatchers (Ficedula hypoleuca) found that changes in female but not male plumage ornaments were affected by climate during breeding, such that cold and rainy breeding seasons decreased female ornamentation, likely re ecting a greater cost of breeding in those years 59 .…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, males may prioritize allocating resources to ornamentation, even in suboptimal environmental or physiological condition, because they have the most to gain from sexual ornamentation, in the form of attracting mates and increasing paternity rates. According to this view, bill color in American gold nches (Spinus tristis) was found to re ect individual differences in female immune function but not in males, who consistently invest in bill coloration irrespective of immune function 12 , and a recent eld study with pied ycatchers (Ficedula hypoleuca) found that changes in female but not male plumage ornaments were affected by climate during breeding, such that cold and rainy breeding seasons decreased female ornamentation, likely re ecting a greater cost of breeding in those years 59 .…”
Section: Discussionmentioning
confidence: 98%
“…It has been previously shown that plumage traits in the study populations show marked phenotypic plasticity and are affected by previous conditions in both the breeding and wintering ranges (Moreno et al . 2019). Plastic individual traits interacting with a variable social context may remove any potential for repeatability of mating outcomes (but see male wing patch size for a repeatable trait linked to EPY).…”
Section: Discussionmentioning
confidence: 99%
“…Forehead patch size is highly repeatable across years ( r = .72) (Järvistö et al., 2016) indicating high heritability or a permanent environmental effect on trait expression. Older males have slightly larger forehead patch size than young males (Gálvan & Moreno, 2009; Järvistö et al., 2016), and in addition, an Iberian population very old males tended to reduce their forehead patches (Moreno et al., 2019). Environmental variables experienced during the molting period on the wintering grounds do not predict within‐individual variation of the trait (Järvistö et al., 2016).…”
Section: Proximate Determination Of Color Variationmentioning
confidence: 99%
“…Environmental variables experienced during the molting period on the wintering grounds do not predict within‐individual variation of the trait (Järvistö et al., 2016). There is some evidence that the trait is signaling early‐life individual quality (Dale et al., 1999) and that costs of breeding, that is, unfavorable conditions during breeding and relatively early timing of breeding are followed by forehead patch decrements in males (Moreno et al., 2019). The experimental activation of immune defense reduced the expression of male forehead patch size compared with the control males within the same season (Kilpimaa et al., 2004), indicating that immune defense costs may trade‐off with the maintenance costs of a white forehead patch.…”
Section: Proximate Determination Of Color Variationmentioning
confidence: 99%
See 1 more Smart Citation